2018
DOI: 10.3390/molecules23123218
|View full text |Cite
|
Sign up to set email alerts
|

Mollicellins O–R, Four New Depsidones Isolated from the Endophytic Fungus Chaetomium sp. Eef-10

Abstract: Four new depsidones, mollicellins O–R (compounds 1–4), along with three known compounds 5–7, were isolated from cultures of the fungus Chaetomium sp. Eef-10, an endophyte isolated from Eucalyptus exserta. The structures of the new compounds were elucidated by analysis of the 1D and 2D NMR and HR-ESI-MS spectra. The known compounds were identified by comparison of their spectral data with published values. Compounds 1–7 were evaluated for antibacterial activities against Staphylococcus aureus (sensitive and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…The other signals were attributed to the lactone carbonyl at δ C 166.1 (C-11) and aldehyde function at δ C 193.9 (C-14). These data were similar to those of related depsidones previously isolated from several microorganisms [21,22,23,24] and some species of Garcinia genus [25]. The 1 H NMR spectrum (Table 1) confirmed the presence of two aromatic singlets at δ H 6.85 (1H, s , H-2) and δ H 7.08 (1H, s , H-9), suggesting two penta-substituted aromatic rings.…”
Section: Resultssupporting
confidence: 86%
“…The other signals were attributed to the lactone carbonyl at δ C 166.1 (C-11) and aldehyde function at δ C 193.9 (C-14). These data were similar to those of related depsidones previously isolated from several microorganisms [21,22,23,24] and some species of Garcinia genus [25]. The 1 H NMR spectrum (Table 1) confirmed the presence of two aromatic singlets at δ H 6.85 (1H, s , H-2) and δ H 7.08 (1H, s , H-9), suggesting two penta-substituted aromatic rings.…”
Section: Resultssupporting
confidence: 86%
“…In our research, ethyl acetate extracts of 15 endophytic fungi (15% of total screened) showed inhibitory activity against pathogenic microorganisms. These 15 isolates represent fungal genera previously reported to produce antimicrobial compounds (Ouyang et al, 2018;Kamdem et al, 2018;Yu et al, 2018;Deshmukh, Verekar & Bhave, 2014). However, new bioactive compounds are constantly being discovered from plant endophytes (Rateb et al, 2011;Sayed et al, 2019;Chen et al, 2019a).…”
Section: Antimicrobial Activity Screening Of the Ethyl Acetate Extracts From Endophytic Fungal Culture Filtratesmentioning
confidence: 99%
“…The goal of this study was to isolate fungal endophytes from T. chinensis Baker of Qinling Mountains region and to screen these fungi for antimicrobial activities and identify compounds using high performance liquid chromatography (HPLC) and ultraperformance liquid chromatography-quadrupole-time of flight mass spectrometry (UPLC-QTOF MS) analyses. The Qinling Mountains (32 • 30 −34 • 45 N, 104 • 30 −112 • 45 E), which is mainly located in the south of Shaanxi province in central China, is the most important natural climatic boundary between the subtropical and warm temperate zones of China, and supports an astonishingly high biodiversity (Ma et al, 2018;Yuan et al, 2017;Huang et al, 2016;Wang et al, 2018). T. chinensis Baker grows in the valleys at altitudes of 500-2,400 m in Qinling Mountains region.…”
Section: Introductionmentioning
confidence: 99%
“…Amikacin was used as a positive control. The minimum inhibitory concentrations (MIC) of the compounds and positive control were determined in sterile 96-well plates using the microculture tetrazolium (MTT) assay as described previously (Ouyang et al, 2018;Zhao et al, 2010). The synergistic antibacterial effects of terphenyllin (2) with different compounds were determined by the same method.…”
Section: Antibacterial Assaymentioning
confidence: 99%
“…Radical scavenging assay was determined by a microplate spectrophotometric method based on the reduction of a methanol solution of DPPH according to our previous reports (Ouyang et al, 2018). Inhibition (%) of free radical (DPPH) in percent was determined as…”
Section: Antioxidant Assaymentioning
confidence: 99%